Climate-smart forage/feed and Gliricidia sepium intercropping innovations - Gosling, Amanda; Kimaro, Anthony; Cramer, Laura K. (2024)
This presentation on Climate-Smart Forage and Feed Innovations was co-developed with the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) Tanzanian team to accelerate the spillover process of validated AICCRA technologies. The training content drew upon knowledge materials sourced from the AICCRA Ethiopia and Zambia teams and their respective project partners (Africa Research in Sustainable Intensification for Next Generation (RISING), and Community Markets for Conservation (COMACO) and Mediae, respectively), as well as those provided by CIFOR-ICRAF. The training slides cover four main areas: - Introduction – Tanzania’s climate, land degradation and food security context and the importance of climate-smart livestock management. - Integrated forage cultivation – selecting and integrating forage in a farm system. - Fodder trees – the benefits of fodder trees and how they are climate smart with a focus on establishing and managing Gliricidia sepium. - Livestock feed requirements – estimating feed requirements for smallholder farms and the benefits of using improved feeding troughs and how to construct them.